Counterintuitive Range Shifts May Be Explained by Climate Induced Changes in Biotic Interactions - Inna Osmolovsky; Zoe A. Xirocostas; Giancarlo M. Chiarenza; Angela T. Moles (Global Change Biology, 2025)
Many organisms are expected to shift their ranges uphill, toward the poles or to deeper waters in response to climate change. However, over a third of species exhibit counterintuitive range shifts—toward the equator, downhill or to shallower waters. Despite the prevalence and potential importance of counterintuitive shifts, they are seldom predicted by the species distribution models on which conservation decisions often rely, and we have remarkably few hypotheses as to why species might exhibit counterintuitive shifts. To address this, we propose the ‘Interaction Opportunists Hypothesis’, which formalises the idea that counterintuitive shifts could arise from climate change induced changes in biotic interactions at the warm edge of species' distributions. Reductions in antagonistic interactions, increases in positive interactions or changes in the type or outcome of biotic interactions could make previously unsuitable habitats viable parts of a species' range. Biotic interactions may additionally drive lags in range shifts and the persistence of some species in current habitats despite the changing climate. Understanding the role of biotic interactions is thus crucial for improving forecasting of the rate, direction and vulnerability of range shifting species, aiding conservation and climate mitigation efforts. Our hypothesis provides a generalisable framework to explain counterintuitive shifts across diverse systems and contexts.